Hubungan Motivasi Belajar dengan Konsentrasi Belajar pada Mahasiswa Bahasa Jepang Universitas Riau (Penelitian Korelasi pada Mahasiswa Semester IV Prodi Pendidikan Bahasa Jepang di Universitas Riau) - Merri Silvia Basri; Adisthi Martha Yohani; Intan Suri (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2022)
Concentration is one of the things that can affect the learning process. Concentration in learning is generally related to the motivation of students. If the motivation is good, then the correlation with the interest and concentration of students' learning will increase. This research is a correlational research with a quantitative approach. The data in this study were obtained by providing two types of instruments, namely a learning motivation test and a concentration test. The results of this study indicate that there is a positive influence between learning motivation and learning concentration of students of the Japanese Language Education Program at the Universitas Riau in the 2021/2022 academic year of 0.619 with a moderate or adequate category. This shows that the better the student's learning motivation, the better the student's learning concentration will be.